Geochemical Correlation of Coeval Volcanic and Plutonic Rocks from the Incrementally Emplaced Jackass Lake Pluton, Sierra Nevada Batholith, CA. - Gauer, Anne K. (My University, 2009)
The Jackass Lake Pluton (JLP) is located in the central part of the Sierra Nevada batholith, CA. The JLP is characterized as a suite of intrusions that range in composition from quartz diorite to leucogranite with granodiorite the dominant composition. Trends in geochemical data suggest that the metavolcanic suite is geochemically related to the primary JLP suite.
Color posters with text, map, and charts describing research conducted by Anne K. Gauer, advised by Geoffrey S. Pignotta.
Keywords: Jackass Lake (Calif.); Sierra Nevada (Calif. and Nev.)--Geology.; Intrusions (Geology)--Sierra Nevada (Calif. and Nev.); Posters; Volcanic ash, tuff, etc.--Sierra Nevada (Calif. and Nev.)